Daya Antibakteri Tepung Cacing Tanah (Lumbricus rubellus) Terhadap Pertumbuhan Bakteri Vibrio harveyi Secara In Vitro [Antibacterial Activity Of Earthworm Powder (Lumbricus rubellus) To Vibrio harveyi Growth's In Vitro] - Wahju Tjahjaningsih; Yudi cahyoko; Ekasari Ekasari (Faculty of Fisheries and Marine Universitas Airlangga, 2012)
Abstract Vibrio harveyi is the most common pathogenic agent of Penaeus monodon and causing large economic losses to the shrimp farming industry. Antibiotic has been used as the diseases treatment, but it has been banned due to the side effects. This problem was required an alternative solution by using natural material, such as earthworm powder (L. rubellus). This research was conducted to know the bacterial growth inhibition V. harveyi by using earthworm powder (L. rubellus). The research method is experimental and data analysis done descriptively. Inhibition of V. harveyi growth was tested using disc diffusion method. Earthworm powder concentrations are 0, 25, 50, 75, 100 % (w/v) and chloramphenicol disc (30µg), each treatment was repeated three times. The main parameter observed was the size of diameter inhibition zone (mm) which formed around the disc paper after incubation within 24 hours. The data analysis was done descriptively by comparing sensitivity level each treatment. Results showed that earthworms powder (L. rubellus) from the lowest concentration (25% w/v) to the highest concentration (100% w / v) were not able to inhibit V. harveyi growth.